A Narrative-Relational Approach to the Problem of Evil and the Suffering it Engenders. Issue 1 (2nd January 2016) - Whitehead, Jason
Abstract : Susan Nelson (2003) offered a helpful synopsis of the common ways theologians and others have explored the problem of evil; her five paradigms concerning the problem of evil are helpful tools in teaching theodicy and tragedy. Each paradigm explains different points of view on the problem of evil. While her work provides descriptive and critical approaches to each paradigm, it lacks a dynamic method of interacting with these paradigms in practical theological terms. In this article, I propose utilizing a multi-lens approach that underscores the collective, communal and local, and personal lenses that influence our interpretations of evil and suffering, helping both care-giver and care-seeker connect to the impact of complex multi-layered narratives. Grounded in process-relational theology, narrative theories of identity and therapy, and intercultural pastoral care, this approach describes a tool for assessment and reflection on our own beliefs about the problem of evil so that we might be present to another's beliefs.